Badania kliniczne i doświadczalne w chorobach serca, płuc i naczyńEarly results of heart transplantation in the Silesian Centre for Heart Disease in the light of current recommendations - Zakliczyński, Michał; Barańska-Kosakowska, Anna; Przybylski, Roman; Pacholewicz, Jerzy; Wojarski, Jacek; Nożyński, Jerzy; Konecka-Mrówka, Dominika; Świerad, Marcin; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
Aim: The aim of the study was to assess early results of heart transplantation during the first 18 months after introduction of the new immunosuppressive protocol, suggesting preferential use of mycophenolate mofetil (MMF) instead of azathioprine, and suggesting individualization of the decision to use cyclosporine-A (CyA) or tacrolimus (TAC) as part of primary immunosuppression. Material and Methods: Our retrospective analysis involved the results of all 53 heart transplantations performed in the Silesian Centre for Heart Disease between 1st January 2007 and 30th June 2008. Based on primary immunosuppression patients were divided into the CyA group (n=22, 51±10 y/o, 21 M/1F), and the TAC group (n=28, 38±17 y/o, 20M/8F); 3 patients did not receive any calcineurin inhibitors. We assessed overall survival, acute rejection occurrence, renal function, and infection occurrence. Results: 1-year survival was 89%. All 6 deaths occurred during the 1st month post transplantation, and were related to a primary failure of the graft. At least one episode of significant cellular rejection (ł3A according to the ISHLT grading system) was observed in 22 patients (47%), including 10 patients from the CyA group (45%), and 12 patients from the TAC group (48%, p=0.91). Average number of rejection episodes ł3A was 0.6±0.7 in the whole group, and was identical in number when compared between CyA and TAC groups (p=0.97). At the end of the observation none of the patients required renal replacement therapy and serum creatinine concentration was: 110±46 in the whole group, 108±29 in the CyA group, and 104±49 µmol/l in the TAC group (p=0.79). Bacterial and viral infection rate was 34 and 30% respectively in the whole group, and it was equally distributed between CyA and TAC groups. Conclusions: Adjustment of immunosuppressive therapy to current worldwide practice allows one to achieve acceptable early survival, rate of rejection and immunosuppression-related complications.